Comparative analysis of the Music Education curriculum in Primary Education in Spain according to the LOMLOE. Exploring the construct of creativity - Almunia Borruel, José Ángel; Casanova López, Óscar (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2024)
The LOMLOE has made significant changes in the structure of the education system, especially affecting the teaching of Music Education in Primary Education. This article conducts a qualitative analysis through a documentary review of the current regulations in different regions. Its main objective is to understand the position of music education across the country and determine the learning objectives sought in students. Additionally, possible educational differences based on geographical location are examined. The study focuses on curriculum components and time allocation, with special emphasis on the construct of creativity as a means to enhance autonomy, musical comprehension, and expression in students, as well as their overall development. Furthermore, through the literature review of legislative texts, potential implications that will impact the future of Music Education in this educational stage are identified.
Keywords: Music Education; Primary Education; curriculum; creativity; educational legislation